A new micropterous species of Physoderes from Fiji Islands (Hemiptera: Heteroptera: Reduviidae: Physoderinae) - Davranoglou, Leonidas Romanos (Zootaxa, 2014)
Physoderes manni sp. nov. (Hemiptera: Heteroptera: Reduviidae: Physoderinae) is described from Viti Levu, Fiji and represents the first record of microptery in the subfamily. The relationship of Ph.manni sp. nov. with its congeners, as well as the evolutionary and ecological significance of the micropterous wing condition are discussed.